1999
DOI: 10.1097/00002030-199912240-00007
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of reverse transcriptase inhibitors or a switch from reverse transcriptase to protease inhibitors resulted in a fast reappearance of virus strains with a reverse transcriptase inhibitor-sensitive genotype

Abstract: The results of this study indicate the sustained lower fitness of mutant strains in vivo. As a result, wild-type virus remains capable of outcompeting the RT or protease mutant strains very fast after removal of the drug. These findings highlight the importance of 'treatment history' in addition to genotypic and phenotypic markers determined at one time-point, when making therapeutic decisions for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(66 citation statements)
references
References 6 publications
2
64
0
Order By: Relevance
“…Furthermore, phylogenetic analysis of the nucleotide sequences of intermediate viruses revealed that those with fewer resistance mutations were clearly more closely related to wild-type viral sequences, excluding the possibility of selective reversion of resistance mutations or recombination in these cases. The rapid emergence of fully wild-type virus detected by standard genotypic analysis in this and in prior studies (11,32) and the rapid virus rebound that follows the interruption of an apparently fully suppressive antiretroviral therapy (28) further supports the conclusion that treated patients can continue to harbor strains lacking the full complement of resistance mutations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, phylogenetic analysis of the nucleotide sequences of intermediate viruses revealed that those with fewer resistance mutations were clearly more closely related to wild-type viral sequences, excluding the possibility of selective reversion of resistance mutations or recombination in these cases. The rapid emergence of fully wild-type virus detected by standard genotypic analysis in this and in prior studies (11,32) and the rapid virus rebound that follows the interruption of an apparently fully suppressive antiretroviral therapy (28) further supports the conclusion that treated patients can continue to harbor strains lacking the full complement of resistance mutations.…”
Section: Discussionsupporting
confidence: 75%
“…Correspondingly, it has been observed that in patients who undergo STI following the development of resistant virus, an apparent replacement of the resistant plasma quasi-species by wild-type genomes occurs in most cases (10,11,32). In this study, we have shown that in most patients undergoing STI, small proportions of residual resistant viruses are still detectable at times when conventional bulk-plasma virus genotyping detected only wild-type sequences.…”
Section: Discussionmentioning
confidence: 51%
“…This is similar to how resistance is selected when an individual is receiving treatment (28). Rapid reversions of acquired TDF and FTC mutations have been observed in humans after stopping therapeutic treatment (29)(30)(31). Therefore, resistant viruses selected while on PrEP may also be rapidly outcompeted by the wild-type strains once the pressure of PrEP is removed.…”
Section: (Materials and Methods)mentioning
confidence: 68%
“…When this selective pressure is removed, the emergence of drug-sensitive quasispecies may be expected, as they would be predicted to have a higher fitness in a drug-free environment (9,15,19,20,22,25,34,40,42,43). This rationale led to the many structured treatment interruption (STI) studies carried out on patients with treatment failure and multidrug-resistant viruses (10,12,16,26,45,59). In those cohorts, a rise in plasma viral load and a concomitant fall in CD4 ϩ cell count was observed after treatment interruption; in approximately half of the patients, drug susceptibility shifted from resistant to sensitive.…”
mentioning
confidence: 99%